A new algorithm for implementing message authentication and integrity in software implementations - Alaa Wagih Abdul Qader; Israa Ezzat Salem; Haider Rasheed Abdulshaheed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
IT systems and data that you store, and process are valuable resources that need protection. Validation and reliability of information are essential in networks and computer systems. The communicating is done by two parties via an unsafe channel require a way to validate the data spent by one party as valid (or unaltered) by the other party. In our study, we suggest new one-way defragmentation algorithm to implement message authentication and integration in program execution. These software applications are readily available and freely available because most of the hash functions are faster than their existing radioactive blocks.